2015
DOI: 10.7868/s0555109915020221
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Degradation of Glyphosate Herbicides (Review)

Abstract: This review analyzes the issues associated with biodegradation of glyphosate (N-(phosphonomethyl)glycine), one of the most widespread herbicides. Glyphosate can accumulate in natural environments and can be toxic not only for plants but also for animals and bacteria. Microbial transformation and mineralization ofglyphosate, as the only means of its rapid degradation, are discussed in detail. The different pathways of glyphosate catabolism employed by the known destructing bacteria representing different taxono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 59 publications
6
82
0
7
Order By: Relevance
“…This is indicative that 14 C remained associated with the phosphonic acid moiety despite microbial degradation. Therefore, GPS degradation within the Commerce and Sharkey soils takes place mainly via the AMPA pathway, which is consistent with the findings of others (Borggaard and Gimsing, 2008; Sviridov et al, 2015). To determine the extent of degradation of solid‐phase GPS, residual extracts were analyzed for the presence of both GPS and AMPA, with the results given in Table 3.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is indicative that 14 C remained associated with the phosphonic acid moiety despite microbial degradation. Therefore, GPS degradation within the Commerce and Sharkey soils takes place mainly via the AMPA pathway, which is consistent with the findings of others (Borggaard and Gimsing, 2008; Sviridov et al, 2015). To determine the extent of degradation of solid‐phase GPS, residual extracts were analyzed for the presence of both GPS and AMPA, with the results given in Table 3.…”
Section: Resultssupporting
confidence: 92%
“…Several factors are associated with the rate and magnitude of GPS degradation, such as total microbial biomass (Franz et al, 1997; Rueppel et al, 1977) and the presence of specific microbial species (Gimsing et al, 2004b). Since GPS degradation in soils is mainly attributed to biotic processes (Sviridov et al, 2015), either general microbial activity is greater in the Sharkey soil or population dynamics are such that sorbed‐phase GPS is more readily bioavailable.…”
Section: Resultsmentioning
confidence: 99%
“…A. 8) (Pipke et al, 1980;Shinabarger and Braymer, 1986;Fitzgibbon and Braymer, 1988;Liu et al, 1991;Dick and Quinn, 1995;Penaloza-Vazquez et al, 1995;Singh and Walker, 2006;Castro Jr. et al, 2007;Sviridov et al, 2011Sviridov et al, , 2015Hove-Jensen et al, 2014;Kryuchkova et al, 2014). The bacteria were propagated on M9 minimal medium agar plates without glyphosate (− GS) and with 10 mM glyphosate (+ GS) and incubated for 72 h at 37 C. Four mutants were randomly selected and evaluated for their growth behaviour on M9 plates without and with 10 mM GS supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed the degradation of glyphosate into amino acids in a water–sediment system, suggesting a role of sediment during microbial degradation. In systems where AMPA is not further degraded, it may serve as an indicator for glyphosate degradation . In order to study the effects of glyphosate on the microbiome, but also to estimate the actual exposure of the herbicide, methods for accurate quantitation in complex matrices are required.…”
Section: Introductionmentioning
confidence: 99%